Trajectories of functional and structural myocardial parameters in post-COVID-19 syndrome—insights from mid-term follow-up by cardiovascular magnetic resonance - Gröschel, Jan; Grassow, Leonhard; van Dijck, Phillip; Bhoyroo, Yashraj; Blaszczyk, Edyta; Schulz-Menger, Jeanette (Frontiers in Cardiovascular Medicine, 2024)
Introduction Myocardial tissue alterations in patients with post-Coronavirus disease 2019 syndrome (PCS) are often subtle and mild. Reports vary in the prevalence of non-ischemic and ischemic injuries as well as the extent of ongoing myocardial inflammation. The exact relevance of these myocardial alterations is not fully understood. This study aimed at describing the trajectories of myocardial alterations in PCS patients by mid-term follow-up with cardiovascular magnetic resonance (CMR). Methods This study entails a retrospective analysis of symptomatic PCS patients referred for follow-up CMR between August 2020 and May 2023 due to mildly affected or reduced left or right ventricular function (LV and RV, respectively) and structural myocardial alterations, e.g., focal and diffuse fibrosis, on baseline scans. Follow-up CMR protocol consisted of cine images and full coverage native T1 and T2 mapping. Baseline and follow-up scans were compared using t-tests or Wilcoxon tests. Post-hoc analysis was carried out in a subgroup based on the change of LV stroke volume (SV) between scans. Results In total, 43 patients [median age (interquartile range) 46 (37–56) years, 33 women] received follow-ups 347 (167–651) days after initial diagnosis. A decrease in symptoms was recorded on follow-ups (p < 0.03) with 23 patients being asymptomatic at follow-ups [symptomatic at baseline 43/43 (100%) vs. symptomatic at follow-up 21/43 (49%), p < 0.001]. Functional improvement was noted for LV-SV [83.3 (72.7–95.0) vs. 84.0 (77.0–100.3) ml; p = 0.045], global radial [25.3% (23.4%–27.9%) vs. 27.4% (24.4%–33.1%); p < 0.001], and circumferential strains [−16.5% (−17.5% to −15.6%) vs. −17.2% (−19.5% to −16.1%); p < 0.001]. In total, 17 patients had an LV-SV change >10% on follow-up scans (5 with a decrease and 12 with an increase), with LV-SV, RV-SV, and global longitudinal strain being discriminatory variables on baseline scans (p = 0.01, 0.02, and 0.04, respectively). T1- or T2-analysis revealed no changes, remaining within normal limits. Conclusion Symptomatic load as well as blood pressures decreased on follow-up. CMR did not detect significant changes in tissue parameters; however, volumetric, specifically LV-SV, and deformation indexes improved during mid-term follow-up.